(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper analyzes the quality of English language education in public schools in Uzbekistan. The study examines the current state of English language instruction, identifies key challenges, and explores possible solutions and best practices. The findings reveal that the quality of education largely depends on teachers’ qualifications, availability of educational materials, and the effectiveness of practical language activities. The study provides recommendations for enhancing English language instruction in Uzbekistan’s public schools.